Equipment set for all-seasonal processing of poultry manure. Issue 3 (December 2021) - Gusev, V; Zazykina, L; Sysoeva, I
Abstract: New equipment set for the processing of manure, the main waste of poultry farms, into a range of ancillary products with predetermined properties and parameters is described. This technology decreases the emission of harmful substances into the atmosphere. The method of preparation of manure for the usage as a solid fuel with decreased expenses for drying was developed; this method allows for the significant decrease of nitrogen content in the manure (resulting in the decreased nitrogen emission at burning). The method involves the preliminary mixing of the manure with a natural absorbent (3-5% of the dry matter of manure) sieved through the 0.2 mm screen; separation of the mixture (by centrifuging or pressing) to solid fraction (moisture content 45-56%) and liquid fraction; drying of the solid fraction in a cylinder drier to moisture content 12-22%; the final product can also be pelleted. A part of the product can be burned in a furnace to produce the heat for the drying of the solid fraction; liquid fraction can be further processed in a coagulator to extract protein or can be used as a liquid fertilizer or ingredient of the liquid substrates in the hydroponic greenhouses.